A NOVEL COARSE-MESH METHOD APPLIED TO NEUTRON SHIELDING PROBLEMS USING THE MULTIGROUP TRANSPORT THEORY IN DISCRETE ORDINATES FORMULATIONS - Rafael Barbosa Libotte; Hermes Alves Filho; Ricardo Carvalho de Barros (Brazilian Journal of Radiation Sciences, 2021)
In this paper, we propose a new deterministic numerical methodology to solve the one-dimensional linearized Boltzmann equation applied to neutron shielding problems (fixed-source), using the transport equation in the discrete ordinates formulation (SN) considering the multigroup theory. This is a hybrid methodology, entitled Modified Spectral Deterministic Method (SDM-M), that derives from the Spectral Deterministic Method (SDM) and Diamond Difference (DD) methods. This modification in the SDM method aims to calculate neutron scalar fluxes with lower computational cost. Two model-problems are solved using the SDM-M, and the results are compared to the coarse-mesh methods SDM, Spectral Green's Function (SGF) and Response Matrix (RM), and the fine-mesh method DD. The numerical results were obtained in the programming language JAVA version 1.8.0_91.